The Effect of Using Eco-Enzymes As Starters on The Physical and Nutritional Quality of Corn Cob Fermentation - Rohmiyatul Islamiyati; Budiman Nohong (Journal of Global Innovations in Agricultural Sciences)
Corn cobs are a potential source of fiber for ruminants, yet it has not been optimally utilized due to its low digestibility. The nutritional content and digestibility of corn cobs could be maximized through microbial activity during the fermentation process. By improving both, corn cobs could be used as valuable fiber sources for ruminants. The microbial activity could be improved by adding starters on the substrate. This study aims to identify the effect of eco-enzymes as starters on the physical and nutritional quality of corn cobs fermentation. This study used a completely randomized design with four treatments namely P0: corn cob without eco-enzyme; P1: corn cob + Eco-enzyme 1,5%; P2: corn cob + Eco-enzyme 3%; and P3: corn cob + Eco-enzyme 4,5% with three replications for each treatment. The results show that using eco-enzyme as a starter could prevent fungal growth in all treatments. In addition, it also improved fermentation quality on T2 and T3 treatment. Using eco-enzyme as a starter also significantly (P<0.05) decreases pH and crude fiber content and increases crude protein, ether extract, nitrogen-free extract, and total digestible nutrient of fermented corn cobs. It can be concluded that providing eco-enzyme starters at different levels can improve the quality of the final results of corn cob fermentation. Keywords: Agricultural waste, corn cobs, ruminant, eco-enzyme, fermentation, physical quality, nutritional quality